Long-Term Impact of Body Mass Index on Survival of Patients Undergoing Cardiac Resynchronization Therapy: A Multi-Centre Study - Papageorgiou, Nikolaos; Briasoulis, Alexandros; Barra, Sergio; Sohrabi, Catrin; Lim, Wei-Yao; Agarwal, Sharad; Oikonomou, Evaggelos; Duehmke, Rudolf; Roubicek, Tomas; Polasek, Rostislav; Behar, Jonathan M; Rinaldi, Christopher A; et al. (The American journal of cardiology, 2021)
Obesity is a risk factor for heart failure (HF), but its presence among HF patients may be associated with favorable outcomes. We investigated the long-term outcomes across different body mass index (BMI) groups, after cardiac resynchronization therapy (CRT), and whether defibrillator back-up (CRT-D) confers survival benefit. One thousand two-hundred seventy-seven (1,277) consecutive patients (mean age: 67.0 ± 12.7 years, 44.1% women, and mean BMI: 28.3 ± 5.6 Kg/m2) who underwent CRT implantation in 5 centers between 2000-2014 were followed-up for a median period of 4.9 years (IQR 2.4 to 7.5). More than 10% of patients had follow-up for ≥10 years. Patients were classified according to BMI as normal: <25.0 Kg/m2, overweight: 25.0 to 29.9 Kg/m2 and obese: ≥30.0 Kg/m2. 364 patients had normal weight, 494 were overweight and 419 were obese. CRT-Ds were implanted in >75% of patients, but were used less frequently in obese individuals. The composite endpoint of all-cause mortality or cardiac transplant/left ventricular assist device (LVAD) occurred in 50.9% of patients. At 10-year follow-up, less than a quarter of patients in the lowest and highest BMI categories were still alive and free from heart transplant/LVAD. After adjustment BMI of 25 to 29.9 Kg/m2 (HR = 0.73 [95%CI 0.56 to 0.96], p = 0.023) and use of CRT-D (HR = 0.74 [95% CI 0.55 to 0.98], p = 0.039) were independent predictors of survival free from LVAD/heart transplant. BMI of 25 to 29.9 Kg/m2 at the time of implant was independently associated with favourable long-term 10-year survival. Use of CRT-D was associated with improved survival irrespective of BMI class.
Keywords: nadváha; lidé; Middle Aged; Obesity; Heart Failure; Mortality; míra přežití; Female; defibrilátory implantabilní; srdeční selhání; Body Mass Index; retrospektivní studie; Survival Rate; Heart-Assist Devices; Humans; Defibrillators, Implantable; index tělesné hmotnosti; Cardiac Resynchronization Therapy; Overweight; obezita; srdeční resynchronizační terapie; prostředky srdeční resynchronizační terapie; lidé středního věku; Heart Transplantation; mužské pohlaví; mortalita; ženské pohlaví; Cardiac Resynchronization Therapy Devices; transplantace srdce; Aged, 80 and over; senioři nad 80 let; Male; Aged; Retrospective Studies; podpůrné srdeční systémy; senioři